Cylindrical Lithium Primary Battery

JP7630627B2Active Publication Date: 2025-02-17MAXELL LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023540350
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-08-04
Filing Date
2022-08-02
Publication Date
2025-02-17
Estimated Expiration
2042-08-02

AI Technical Summary

Benefits of technology

【0010】 巻回された電極体の挿入不良が生じにくく高容量な円筒形リチウム一次電池を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007630627000002
    Figure 0007630627000002
  • Figure 0007630627000003
    Figure 0007630627000003
  • Figure 0007630627000004
    Figure 0007630627000004
Patent Text Reader

Abstract

A cylindrical lithium primary battery of the present application comprises an electrode body in which a positive electrode and a negative electrode are spirally wound with a separator interposed therebetween, wherein the positive electrode includes a positive electrode current collector and a positive electrode mixture layer including manganese dioxide as a positive electrode active material on both sides of the positive electrode current collector, the content of manganese dioxide per unit area of the positive electrode mixture layer is 0.205-0.227 g / cm2 per one side of the positive electrode current collector, the negative electrode includes a negative electrode current collector and two lithium layers that are laminated on one side of the negative electrode current collector and divided in the longitudinal direction at intervals of 6-12 mm and have a lithium content per unit area of 0.014-0.017 g / cm2, and the negative electrode is folded back and wound such that the negative electrode current collectors overlap each other and the inner peripheral side ends of the two lithium layers are positioned outside the winding center.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a cylindrical lithium primary battery having an electrode assembly with a wound structure in which lithium is used as the negative electrode. [Background technology]

[0002] With the development of IoT, LPWA (Low Power Wide Area) has been attracting attention in recent years as a technology that reduces the power consumption of IoT devices and enables long-distance wireless communication. LPWA has the advantages of high propagation characteristics and low power consumption, but as its range of application expands to include wearable devices and data transmission from various installation environments, there is a demand for the development of high-capacity batteries that can supply stable power as a power source for these devices regardless of the installation environment.

[0003] Examples of batteries suitable for such purposes include lithium primary batteries (non-aqueous electrolyte primary batteries), and various studies are being conducted to increase the capacity and improve the characteristics of such batteries. For example, Patent Document 1 discloses a cylindrical non-aqueous electrolyte primary battery that has excellent heavy-load pulse discharge characteristics so that it can be used in applications such as gas meter shutoff valves and wireless communications.

[0004] In the battery described in Patent Document 1, the negative electrode has a metallic lithium-containing layer consisting of only one continuous layer on one side of a current collector, and the metallic lithium-containing layer covers 85% or more of the area of ​​the surface of the current collector on which the metallic lithium-containing layer is formed. A lithium-aluminum alloy is formed on at least a part of the surface of the metallic lithium-containing layer opposite the current collector, thereby forming a cylindrical nonaqueous electrolyte primary battery with excellent heavy-load pulse discharge characteristics.

[0005] Furthermore, when a negative electrode is constructed by arranging two sheets of metallic lithium foil spaced apart on the surface of a negative electrode current collector, the negative electrode has uneven thickness, and thus is prone to misalignment when it is superimposed on a positive electrode and a separator and wound into a spiral shape, resulting in poor winding. In contrast, in Patent Document 1, by arranging only one continuous sheet of metallic lithium foil on the surface of the negative electrode current collector, it is possible to suppress misalignment when forming an electrode group with a wound structure, thereby improving the productivity of batteries. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2012-138225 A Summary of the Invention [Problem to be solved by the invention]

[0007] However, in a configuration in which a single continuous metallic lithium foil is disposed on the surface of the negative electrode current collector, when the active material layers of the positive and negative electrodes are thickened to increase the amount of active material per unit area to increase the capacity of the battery, the thickness of the negative electrode sandwiched between the winding core becomes thick when the negative electrode, positive electrode, and separator are wound together. This results in a large central winding diameter, which is the sum of the thickness of the winding core and the thickness of the negative electrode, and the winding diameter of the electrode body wound around the winding core becomes large, albeit slightly, and this causes a problem in that insertion failure is likely to occur when inserting the electrode body into the outer can unless the inner diameter of the outer can is slightly increased.

[0008] The present invention has been made to solve the above-mentioned problems, and has an object to provide a high-capacity cylindrical lithium primary battery that suppresses the occurrence of improper insertion of a wound electrode body. [Means for solving the problem]

[0009] The cylindrical lithium primary battery of the present application includes an electrode assembly formed by spirally winding a positive electrode and a negative electrode with a separator interposed therebetween, the positive electrode includes a positive electrode current collector and a positive electrode mixture layer that is disposed on both sides of the positive electrode current collector and contains manganese dioxide as a positive electrode active material, and the manganese dioxide content per unit area of ​​the positive electrode mixture layer is 0.205 to 0.227 g / cm per one side of the positive electrode current collector. 2 The negative electrode includes a negative electrode current collector and two lithium layers laminated on one surface of the negative electrode current collector and separated by an interval of 6 mm or more and 12 mm or less in the longitudinal direction, and each of the two lithium layers has a lithium content per unit area of ​​0.014 to 0.017 g / cm. 2 the negative electrode is folded back between the two lithium layers at a position close to one of the lithium layers, the negative electrode current collectors overlap each other, and the negative electrode is wound such that the inner peripheral ends of the two lithium layers are positioned outside the winding center. Effect of the Invention

[0010] It is possible to provide a cylindrical lithium primary battery having a high capacity in which insertion failure of the wound electrode body is unlikely to occur. [Brief description of the drawings]

[0011] [Figure 1] FIG. 1 is a vertical cross-sectional view that illustrates an example of a cylindrical lithium primary battery according to an embodiment. [Diagram 2] FIG. 2 is a cross-sectional view of the cylindrical lithium primary battery of FIG. [Diagram 3] FIG. 3 is a partial cross-sectional view that shows a schematic example of an electrode body having a wound structure that constitutes a cylindrical lithium primary battery of the embodiment. [Figure 4] FIG. 4 is a partial cross-sectional view that illustrates a laminate in which a negative electrode current collector, two sheets of metallic lithium foil, and a separator are integrated together, and is used when producing an electrode body with a wound structure that constitutes a cylindrical lithium primary battery of the embodiment. [Diagram 5]FIG. 5 is a diagram for explaining a method for producing a wound electrode body that constitutes a cylindrical lithium primary battery of the embodiment. [Figure 6] FIG. 6 is a diagram for explaining a method for producing a wound electrode body that constitutes a cylindrical lithium primary battery of the embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] An embodiment of the cylindrical lithium primary battery of the present application will be described with reference to the drawings. Fig. 1 is a longitudinal sectional view that typically shows one example of the cylindrical lithium primary battery of this embodiment, Fig. 2 is a transverse sectional view of the cylindrical lithium primary battery shown in Fig. 1, and Fig. 3 is a partial sectional view that typically shows one example of an electrode body of a wound structure that constitutes the cylindrical lithium primary battery of this embodiment.

[0013] 1, the cylindrical lithium primary battery 1 has a bottomed cylindrical outer can 2 made of iron, stainless steel or the like and having an upper opening, an electrode assembly 3 formed by spirally winding a positive electrode 4 and a negative electrode 5 loaded in the outer can 2 with a separator 6 interposed therebetween, a nonaqueous electrolyte, and a sealing body that seals the upper opening of the outer can 2. In other words, the cylindrical lithium primary battery 1 in FIG 1 has power generating elements such as the electrode assembly 3 having a spiral structure in which a positive electrode 4 and a negative electrode 5 are spirally wound with a separator 6 interposed therebetween, and a nonaqueous electrolyte within a space surrounded by the outer can 2 and the sealing body that seals the upper opening of the outer can 2.

[0014] Fig. 2 shows a cross-sectional view of the cylindrical lithium primary battery of Fig. 1. As shown in Fig. 2, the electrode body 3 is formed by winding a long positive electrode 4 and a long negative electrode 5 with a separator 6 interposed therebetween, and is formed into a generally cylindrical shape. In the cylindrical lithium primary battery 1 shown in Fig. 2, the positive electrode 4 has a structure in which two positive electrode mixture sheets 41, 42 are laminated with a positive electrode current collector 43 interposed therebetween. That is, the positive electrode 4 has a structure in which the two positive electrode mixture sheets provide positive electrode mixture layers 41, 42 on both sides of the positive electrode current collector 43, respectively.

[0015] The positive electrode mixture layers 41 and 42 each contain manganese dioxide as a positive electrode active material. In addition to the positive electrode active material, the positive electrode active material layer usually contains a conductive assistant and a binder. Examples of the conductive assistant include graphite and carbon black (Ketjen black, acetylene black, furnace black, etc.), and only one of these may be used, or two or more of them may be used in combination. Examples of the binder include fluororesins such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVDF); rubber-based binders; and the like. In the case of fluororesins such as PTFE and PVDF, they may be of a dispersion type or a powder type, but dispersion types are particularly suitable. In the positive electrode mixture layer, for example, the content of the positive electrode active material is preferably 92 to 97% by mass, the content of the conductive assistant is preferably 2 to 4% by mass, and the content of the binder is preferably 1 to 4% by mass.

[0016] The manganese dioxide content per unit area of ​​the positive electrode mixture layers 41 and 42 is 0.205 to 0.227 g / cm 2 That is, the positive electrode 4 has a manganese dioxide content per unit area of ​​0.205 to 0.227 g / cm on both sides of the positive electrode current collector 43. 2 The manganese dioxide content per unit area in the positive electrode mixture layer is adjusted to 0.205 g / cm per side of the positive electrode current collector. 2 By setting the content of manganese dioxide at 0.227 g / cm per side of the positive electrode current collector, the capacity of the electrode can be increased even if the length of the positive electrode is relatively short. This allows the length (volume) of the separator to be reduced and the proportion of the active material in the positive electrode and negative electrode to be increased, making it easier to design a battery with a high capacity. 2In order to make the porosity of the positive electrode mixture layer larger than necessary, it is necessary to make the porosity of the positive electrode mixture layer larger than necessary. In the former case, the permeability of the electrolyte into the positive electrode mixture layer decreases, and the reactivity of the positive electrode decreases, resulting in a decrease in the load characteristics of the battery. In the latter case, the flexibility of the positive electrode mixture layer decreases, resulting in an increase in defects during winding. For this reason, the manganese dioxide content per unit area contained in the positive electrode mixture layer is 0.227 g / cm per side of the positive electrode current collector. 2 The following applies.

[0017] The density of the positive electrode mixture layer is set to 2.7 g / cm in order to increase the capacity of the battery. 3 It is preferable that the density is 2.8 g / cm or more. 3 More preferably, it is 2.85 g / cm or more. 3 On the other hand, in order to improve the permeability of the non-aqueous electrolyte and prevent a decrease in discharge characteristics, the density of the positive electrode mixture layer is preferably 3.1 g / cm or more. 3 It is preferable that the density is 3.0 g / cm or less. 3 More preferably, it is 2.95 g / cm or less. 3 It is most preferred that:

[0018] The thickness of the positive electrode is, for example, 1.5 mm or more, and in order to maintain flexibility, it is preferably 2 mm or less, and more preferably 1.8 mm or less.

[0019] The positive electrode can be manufactured, for example, by a method in which a conductive auxiliary and a binder are mixed with a positive electrode active material, and water or the like is added as necessary to form a positive electrode mixture (slurry), which is rolled using a roll or the like to form a preliminary sheet, which is dried and pulverized, and then formed into a sheet shape again by roll rolling or the like to form a positive electrode mixture sheet, which is then superimposed on both sides of a current collector, and the positive electrode mixture sheet and the current collector are integrated by a press or the like to form layers made of the positive electrode mixture sheet (positive electrode mixture layers) on both sides of the current collector.

[0020] Specifically, for example, the three are overlapped such that the outer periphery of the current collector is several mm inside the outer peripheries of the two positive electrode mixture sheets, and during winding, a portion 3 to 10 mm from the longitudinal end that is disposed on the winding core side is pressed, thereby producing a positive electrode having positive electrode active material layers on both sides of the current collector.

[0021] The positive electrode is not limited to the positive electrode produced by the above-mentioned method, and may be produced by other methods. For example, the positive electrode may be produced by a method in which a positive electrode mixture slurry is applied to both sides of a current collector, dried, and, if necessary, pressed to form a positive electrode mixture layer on the current collector.

[0022] Examples of the current collector used for the positive electrode include those made of stainless steel such as SUS316, SUS430, and SUS444, and aluminum, and examples of the form of the current collector include plain woven wire mesh, expanded metal, lath mesh, punched metal, foil (plate), etc. The thickness of the positive electrode current collector is preferably 0.1 to 0.4 mm.

[0023] A paste-like conductive material can be applied to the surface of the positive electrode current collector. When a net-like positive electrode current collector having a three-dimensional structure is used, the current collecting effect is significantly improved by applying the conductive material, as in the case of using a material essentially consisting of a flat plate such as a metal foil or punched metal. This is presumably due to the effective use of not only the path in which the metal part of the net-like current collector directly contacts the positive electrode mixture layer, but also the path via the conductive material filled in the mesh.

[0024] The conductive material may be, for example, silver paste, carbon paste, etc. As the binder for the conductive material, it is preferable to use a heat-resistant material such as water glass or an imide-based binder, since this allows drying at a high temperature exceeding 200° C. to remove moisture from the positive electrode mixture layer.

[0025] The capacity of the negative electrode must be increased to match the capacity of the positive electrode mixture layer. The lithium layer that becomes the active material layer of the negative electrode must have a lithium content per unit area of ​​0.014 to 0.017 g / cm. 2 is adjusted to.

[0026] In order to keep the ratio between the positive electrode capacity and the negative electrode capacity within a certain range, the ratio of the lithium content per unit area of ​​the lithium layer to the manganese dioxide content per unit area of ​​the positive electrode mixture layer (per one side of the positive electrode current collector) is preferably 0.067 to 0.077 by weight.

[0027] However, since the positive electrode with a high capacity as described above has a certain thickness, for example, a thickness of 1.5 mm or more, when a negative electrode in which a continuous metallic lithium foil is arranged on one side of a negative electrode current collector is used as in Patent Document 1, the thickness of the negative electrode sandwiched between the winding cores is thickened by the thickness of the metallic lithium foil (for example, about 0.3 mm). Therefore, the winding center diameter becomes slightly larger, and when a thick positive electrode is used, it becomes difficult to adjust the winding diameter of the wound electrode body to a certain value or less. As a result, unless the inner diameter of the outer can is slightly increased, insertion failure is likely to occur when inserting the electrode body into the outer can, which becomes a factor that hinders high capacity.

[0028] On the other hand, in this embodiment, by configuring the negative electrode as follows, it is possible to solve the above problems and achieve a high capacity battery.

[0029] The negative electrode 5 has a structure in which two lithium layers 51, 51 made of metallic lithium foil are laminated on one side of one negative electrode current collector 52. The negative electrode current collector can be made of foil such as copper, nickel, iron, or stainless steel. The thickness of the negative electrode current collector is preferably as thin as possible, and specifically, it is recommended that the thickness is, for example, 25 μm or less. On the other hand, if the negative electrode current collector is too thin, it is likely to break, so the thickness of the negative electrode current collector is preferably 5 μm or more. In addition, it is preferable that the width of the negative electrode current collector is the same as or wider than the width of the metallic lithium foil constituting the lithium layer. In addition, it is preferable that the area of ​​the negative electrode current collector is 100% or more of the area of ​​the lithium layer. By making the area of ​​the negative electrode current collector as described above, the width and length of the negative electrode current collector are the same as or larger than the width and length of the lithium layer, so that even if a crack occurs in the metallic lithium foil during discharge, it is possible to prevent the electrical connection from being broken.

[0030] On the other hand, since the larger the proportion of the area on the negative electrode current collector where the lithium layer is not laminated, the lower the battery capacity, the area of ​​the negative electrode current collector is preferably 120% or less of the area of ​​the lithium layer, i.e., the area of ​​the lithium layer laminated on the negative electrode current collector is preferably 83% or more of the area of ​​the negative electrode current collector.

[0031] The surfaces of the two lithium layers 51, 51 on the separator side may be alloyed with aluminum, and thus the load characteristics of the battery can be improved, so that a lithium-aluminum alloy may be formed on the surface of the lithium layer. When forming a lithium-aluminum alloy on the surface of the lithium layer on the separator side, it is preferable that the lithium-aluminum alloy is formed on 90% or more of the area of ​​the entire lithium layer. In order to enhance the effect of improving the load characteristics, it is preferable that the ratio of the total amount of aluminum to the total amount of lithium in the entire lithium layer (including lithium in the lithium-aluminum alloy) is 0.095 or more by weight. On the other hand, since the discharge capacity of the negative electrode decreases as the proportion of aluminum increases, it is preferable that the weight ratio is 0.105 or less from the viewpoint of increasing the capacity.

[0032] A negative electrode is produced by laminating aluminum foil on metallic lithium foil, and a battery is assembled using the negative electrode, whereby a lithium-aluminum alloy can be formed on the surface of the lithium layer within the battery.

[0033] The thickness of the metallic lithium foil used in producing the negative electrode is, for example, 0.25 to 0.35 mm, and the thickness of the aluminum foil is, for example, 5 to 20 μm. The two lithium layers 51, 51 are composed of two metallic lithium foils 51, 51 separated by an interval of 6 mm to 12 mm in the longitudinal direction on the negative electrode current collector 52. That is, between the two lithium layers 51, 51, there is a portion with a width of 6 mm to 12 mm in the longitudinal direction (winding direction) where no lithium layer is formed and the negative electrode current collector 52 is exposed.

[0034] As shown in FIG. 2, in the electrode body 3, one long negative electrode 5 is folded back between two lithium layers 51, 51 and at a position close to one of the lithium layers (the lithium layer facing the positive electrode mixture layer 42 on the inner surface side of the positive electrode 4), for example, at a position about 1 mm from the inner circumferential end (the end at the winding start side) of the lithium layer, so as to substantially follow the winding core removed after winding, and the negative electrode current collectors are overlapped with each other, and the inner circumferential ends of the two lithium layers 51, 51 are each positioned outside the winding center 18. Here, the winding center 18 refers to the part of the negative electrode that is sandwiched and wound by the winding core (for example, width: about 3 mm) during winding, and its length is approximately the same as the width of the winding core. As a result, the thickness of the negative electrode sandwiched by the winding core becomes thinner than when the lithium layer is formed as a single continuous body, so that the winding diameter of the wound electrode body can be reduced. In addition, by arranging the two lithium layers 51, 51 at a distance of 6 mm or more in the longitudinal direction, it is possible to form a portion where no lithium layers are laminated with a certain width or more in the negative electrode current collector on the inner side of the stacked negative electrode current collectors, from the winding center toward the positive electrode mixture layer 41 on the outer surface side of the positive electrode 4. The width of the portion where no lithium layers are laminated may be appropriately adjusted depending on the length from the winding center to the positive electrode mixture layer 41 on the outer surface side, but is preferably 2 mm or more from the winding center, and more preferably 4 mm or more.

[0035] In the negative electrode current collector on the inner surface side, the portion between the winding center 18 and the end of the winding start side of the positive electrode mixture layer 41 of the positive electrode 4 does not face the positive electrode, so that by not laminating a lithium layer on this portion of the negative electrode current collector, lithium not involved in discharge can be reduced and discharge efficiency can be improved. Furthermore, by reducing the thickness of the winding start portion of the negative electrode, the winding diameter of the wound electrode body can be made smaller. From these viewpoints, the distance between the two lithium layers 51, 51 is preferably 8 mm or more.

[0036] In the electrode assembly 3, by configuring the negative electrode 5 as described above, it is possible to prevent insertion failure when inserting the wound electrode assembly 3 into the outer can 2. On the other hand, if the gap between the two lithium layers 51, 51 is too wide, the start of the winding of the positive electrode mixture layer will not face the lithium layer, which may result in a decrease in discharge capacity. To prevent the above problem, the gap between the two lithium layers 51, 51 is set to 12 mm or less, and preferably 10 mm or less.

[0037] In view of the above, the distance between the two lithium layers 51, 51 is preferably set to 8 mm or more and 10 mm or less.

[0038] 1 and 2, the separator 6 is shown as having a single layer structure, but in this embodiment, as the thickness of the positive electrode increases, it becomes necessary to consider the risk of short circuit. For this reason, in this embodiment, as shown in Fig. 3, the separator 6 inserted between the positive electrode 4 and the negative electrode 5 is preferably multi-layered, for example, composed of two resin microporous films 61 and 62. The two separators may also be a combination of a resin microporous film and a nonwoven fabric.

[0039] As shown in FIG. 1, the sealing body of the cylindrical lithium primary battery 1 has a cover plate 7 fixed to the inner periphery of the upper opening of the outer can 2, a terminal body 9 attached to an opening in the center of the cover plate 7 via an insulating packing 8 made of polypropylene or the like, and an insulating plate 10 arranged under the cover plate 7. The insulating plate 10 is formed in a round dish shape that opens upward with an annular side wall 12 standing on the periphery of a disk-shaped base part 11, and a gas vent 13 is opened in the center of the base part 11. The cover plate 7 is fixed to the inner periphery of the upper opening of the outer can 2 by laser welding or by crimp sealing via a packing while being received on the upper end of the side wall 12. As a measure against a sudden increase in the internal pressure of the battery, a thin-walled part (vent) can be provided on the cover plate 7 or the bottom part 2a of the outer can 2. The positive electrode 4 and the lower surface of the terminal body 9 are connected by a positive electrode lead body 15. Furthermore, negative electrode lead body 16 attached to negative electrode 5 is welded to the upper inner surface of outer can 2. Furthermore, at bottom 2a of outer can 2, insulating plate 14 made of resin is disposed.

[0040] In Fig. 1, the terminal body 9 is not hatched to indicate a cross section in order to make the drawing easier to see. Note that the positive electrode lead body 15 and the negative electrode lead body 16 are disposed at positions outside the cross section of Fig. 1, and therefore do not originally show a cross section.

[0041] The electrode assembly 3 to be inserted inside the exterior can 2 can be produced, for example, by the procedures shown in Figures 4, 5, and 6. Note that in Figures 4, 5, and 6, the separator 6 is shown as a single-layer structure, and the two separators 61, 62 are not distinguished from one another.

[0042] First, as shown in FIG. 4, the adhesive tape 31 and the separator 6 are placed on the upper surface of the central portion of the negative electrode current collector 52 in the longitudinal direction, thereby fixing the separator 6 to the negative electrode current collector 52. The adhesive tape 31 can be a double-sided tape. Next, two metallic lithium foils 51, 51 are pressed and fixed to both sides of the negative electrode current collector 52 in the longitudinal direction, sandwiching the fixed portion of the separator 6. In other words, a portion is provided on one side of the negative electrode current collector 52 where the lithium layer, which is the negative electrode active material, is not formed and the negative electrode current collector 52 is exposed, and the separator 6 is fixed to this exposed portion 30 by the adhesive tape 31. At this time, the width of the exposed portion 30 (the distance between the two metallic lithium foils 51, 51 in the longitudinal direction) is set to 6 mm or more and 12 mm or less, as described above. In this manner, a laminate 32 in which the negative electrode current collector 52, the two metallic lithium foils 51, 51, and the separator 6 are integrated can be obtained.

[0043] When a lithium-aluminum alloy is formed on the surface of the lithium layer, the laminate may be constructed by further laminating an aluminum foil 51b on a metallic lithium foil 51a, as shown in the enlarged view of Fig. 4. That is, the lithium layer 51 shown in the single-layer structure of Figs. 4, 5, and 6 can be a laminate of a metallic lithium foil 51a and an aluminum foil 51b, as shown in the enlarged view of Fig. 4.

[0044] Next, as shown in Fig. 5, the laminate 32 is inserted between the horizontal split grooves 35 of the winding core 33. The width of the horizontal split grooves 35 of the winding core 33 is 2.8 mm. Here, the distance between the left end of the horizontal split grooves 35 of the winding core 33 in Fig. 5 and the end of the metallic lithium foil 51 is approximately 1 mm, and the exposed portion 30, i.e., the portion of the separator 6 fixed by the adhesive tape 31, is positioned between the horizontal split grooves 35 of the winding core 33.

[0045] In the above state, the winding core 33 is rotated in one direction (clockwise in FIG. 5) by about half a turn, and the laminate 32 is wound around the outer circumferential surface of the winding core 33 as shown in FIG. 6. Next, the positive electrode 4 consisting of the positive electrode mixture sheets 41, 42 and the positive electrode current collector 43 is placed on the separator 6 and wound around the winding core 33 together with the laminate 32. After the laminate 32 and the positive electrode 4 are wound around the winding core, the winding core 33 is removed from the wound body, and finally, the winding end of the metallic lithium foil 51 is fixed with a fixing tape. Here, the negative electrode 5 is folded back between the two metallic lithium foils 51, 51 at a position about 1 mm from one of the metallic lithium foils 51, and is wound so that the negative electrode current collectors 52 overlap each other and the inner peripheral ends of the two metallic lithium foils 51, 51 are each positioned outside the winding center 18. The folding position of the negative electrode is preferably within 1.5 mm, and more preferably within 1.0 mm, from one of the metallic lithium foils 51. In this manner, as shown in Fig. 2 and Fig. 6, an electrode body 3 can be obtained in which the positive electrode 4 and the negative electrode 5 are wound with the separator 6 interposed therebetween, with the exposed portion 30 that was sandwiched between the winding cores serving as the winding center portion 18.

[0046] The separator of the cylindrical lithium primary battery of this embodiment is made of a resin microporous film, nonwoven fabric, etc. Examples of resins constituting the separator include polyolefins such as polyethylene (PE) and polypropylene (PP); polyesters such as polyethylene terephthalate (PET) and polybutylene terephthalate (PBT); and polyphenylene sulfide (PPS); and one or more of these can be used.

[0047] The thickness of the separator is preferably 7 μm or more, more preferably 10 μm or more, and preferably 20 μm or less, and more preferably 18 μm or less, in the case of a microporous film, and is preferably 10 μm or more, more preferably 20 μm or more, and preferably 80 μm or less, and more preferably 50 μm or less, in the case of a nonwoven fabric.

[0048] The nonaqueous electrolyte of the cylindrical lithium primary battery of this embodiment is a solution in which a lithium salt such as LiClO4, LiCF3SO3, LiC2F5SO3, LiN(FSO2)2, or LiN(CF3SO2)2 is dissolved in an organic solvent as an electrolyte.

[0049] Examples of organic solvents include cyclic carbonates such as ethylene carbonate, propylene carbonate, butylene carbonate, and vinylene carbonate; chain carbonates such as dimethyl carbonate, diethyl carbonate, and methyl ethyl carbonate; ethers such as 1,2-dimethoxyethane (ethylene glycol dimethyl ether), diglyme (diethylene glycol dimethyl ether), triglyme (triethylene glycol dimethyl ether), tetraglyme (tetraethylene glycol dimethyl ether), methoxyethoxyethane, 1,2-diethoxyethane, and tetrahydrofuran; cyclic esters such as γ-butyrolactone; nitriles; and the like. Only one of these may be used, or two or more may be used in combination. In particular, it is preferable to use the cyclic carbonate and ether in combination.

[0050] As the cyclic carbonate, ethylene carbonate and propylene carbonate are preferably used. As the ether, 1,2-dimethoxyethane is preferably used. In order to ensure good lithium ion conductivity, the concentration of the lithium salt in the non-aqueous electrolyte is preferably 0.3 mol / L or more, more preferably 0.4 mol / L or more, and is preferably 1.2 mol / L or less, more preferably 1.0 mol / L or less.

[0051] In describing the cylindrical lithium primary battery of this embodiment, reference is made to FIGS. 1 to 6. However, these drawings merely show one example of the battery of this embodiment, and the battery of this embodiment is not limited to those shown in these drawings. EXAMPLES

[0052] Hereinafter, the cylindrical lithium primary battery disclosed in the present application will be described in detail based on examples. However, the cylindrical lithium primary battery disclosed in the present application is not limited to the following examples.

[0053] Example 1 [Preparation of positive electrode] First, a positive electrode mixture was prepared in the following manner. 2 2 parts by mass of Ketjen Black "EC300J" (product name) with a molecular weight of 1.001 g / g and 94.5 parts by mass of manganese dioxide with an average particle size of 35 μm as a positive electrode active material were mixed in a dry state using a planetary mixer for 5 minutes, and then water was added in an amount equivalent to 20% (mass ratio) of the total solid content and mixed for another 5 minutes. Next, PTFE dispersion (Daikin Industries, Ltd. "D-1") was added in a ratio of 3.5 parts by mass of PTFE, and finally water was added until the total solid content ratio became 74% by mass, and the mixture was mixed for another 5 minutes to obtain a positive electrode mixture.

[0054] Next, the positive electrode mixture was rolled into a sheet using a roll with a diameter of 250 mm and a temperature adjusted to 125±5° C., and dried in a temperature environment of 105±5° C. until the residual moisture was 2 mass% or less, thereby forming a preliminary sheet. Furthermore, the preliminary sheet was crushed into a powder with a particle diameter of approximately 0.5 mm or less using a crusher, and then rolled again using the roll to obtain a thickness of 0.79 mm and a density of 2.89 g / cm. 3 The manganese dioxide content per unit area of ​​this positive electrode mixture sheet was 0.216 g / cm 2 It was.

[0055] The obtained positive electrode mixture sheet was cut to obtain an inner surface positive electrode mixture sheet (positive electrode mixture sheet 42 in FIG. 2) having a width of 42.5 mm and a length of 67 mm, and an outer surface positive electrode mixture sheet (positive electrode mixture sheet 41 in FIG. 2) having a width of 42.5 mm and a length of 76 mm.

[0056] A stainless steel (SUS316) expanded metal was used for the positive electrode current collector. This expanded metal was cut to a width of 39 mm and a length of 60 mm, and a stainless steel ribbon with a thickness of 0.1 mm and a width of 3 mm was attached to the center of the length by resistance welding as a positive electrode lead body. Furthermore, carbon paste (manufactured by Nippon Graphite Co., Ltd.) was applied to this expanded metal to an extent that the mesh was not crushed, and then dried at a temperature of 105±5°C to obtain a positive electrode current collector. The amount of carbon paste applied after drying was 5 mg / cm. 2 It was made so that:

[0057] Next, with the positive electrode current collector interposed between the positive electrode mixture sheet on the inner surface side and the positive electrode mixture sheet on the outer surface side, only one end in the length direction was fixed, and each positive electrode mixture sheet and the positive electrode current collector were integrated. Specifically, the positive electrode mixture sheet on the inner surface side and the positive electrode mixture sheet on the outer surface side were aligned at one end in the length direction, and the end of the positive electrode current collector was set so that it did not protrude from the end of the two positive electrode mixture sheets, and in that state, the two positive electrode mixture sheets were pressed at a position 5 mm from the end to integrate each positive electrode mixture sheet and the positive electrode current collector. Then, by drying with hot air at 300±10°C for 15 minutes, a sheet-like positive electrode having a thickness of 1.6 mm and a width of 42.5 mm was obtained.

[0058] [Preparation of negative electrode] A metallic lithium foil having a width of 42 mm, a length of 96 mm, and a thickness of 0.29 mm and a metallic lithium foil having a width of 42 mm, a length of 57 mm, and a thickness of 0.29 mm were arranged on a copper foil (negative electrode current collector) having a width of 43 mm, a length of 173 mm, and a thickness of 15 μm, with a 9 mm interval in the longitudinal direction. Furthermore, an aluminum foil having a width of 40 mm, a length of 96 mm, and a thickness of 6 μm and a width of 40 mm, a length of 57 mm, and a thickness of 6 μm were arranged on the metallic lithium foil, respectively, to form a sheet-like negative electrode. The ratio of the area of ​​the aluminum foil to the area of ​​the metallic lithium foil was 95%, and the metallic lithium foil and the aluminum foil were aligned at both ends in the longitudinal direction and at the end in the width direction that would become the bottom side of the battery when inserted into the outer can. A negative electrode lead body made of nickel and having a width of 3 mm, a length of 20 mm and a thickness of 0.1 mm was previously pressure-bonded to the metallic lithium foil.

[0059] In this sheet-shaped negative electrode, the lithium content in the lithium layer is 0.0155 g / cm per unit area. 2 The area of ​​the entire lithium layer was 95% of the area of ​​the negative electrode current collector, and the ratio by weight of the total amount of aluminum to the total amount of lithium contained in the entire lithium layer, including the formed lithium-aluminum alloy, was 0.0995.

[0060] [Preparation of electrode body] Two sheets of PE microporous film (porosity: 46%, air permeability: 200 sec / 100 mL, puncture strength: 380 g) measuring 49 mm in width, 180 mm in length, and 16 μm in thickness were stacked together and used as a separator.

[0061] As shown in Fig. 4, an adhesive tape was applied to the copper foil between the two metallic lithium foils of the sheet-shaped negative electrode, and then the two overlapping PE microporous films were applied to the adhesive tape to obtain a laminate in which a separator was laminated on a sheet-shaped negative electrode. Furthermore, as shown in Fig. 5 and Fig. 6, the part of the laminate to which the adhesive tape was applied was sandwiched between two split winding cores (diameter: 2.8 mm), and the negative electrode and the separator were wound about once, and then the positive electrode was placed and wound so that the fixed end of the positive electrode mixture sheet was on the winding core side, to obtain the electrode body shown in Fig. 2.

[0062] The distance between the folded portion of the negative electrode formed by the winding core during winding and the inner peripheral end of the metallic lithium foil facing the inner surface side of the positive electrode was about 1 mm, and the distance between the inner peripheral end of the metallic lithium foil facing the outer surface side of the positive electrode and the winding center was about 5 mm, and a portion in which the lithium layer was not laminated was formed on the negative electrode current collector with a width of about 5 mm from the winding center toward the positive electrode mixture layer on the outer surface side of the positive electrode. In addition, when winding, the separator was arranged so that one end in the width direction of the separator (the end located on the upper side of the battery) protruded 1.5 mm from the end of the negative electrode (the end located on the upper side of the battery), and the other end of the separator protruding from the positive electrode was folded toward the positive electrode side, so that the end face of the positive electrode was covered with the separator.

[0063] [Battery assembly] The assembly process of a cylindrical lithium primary battery will be described with reference to Fig. 1. A 0.2 mm thick PP insulating plate 14 was inserted into the bottom 2a of a cylindrical exterior can 2 made of nickel-plated stainless steel, and the electrode body 3 was inserted on top of that with the positive electrode lead body 15 facing upward.

[0064] The negative electrode lead body 16 of the electrode body 3 was resistance welded to the inner surface of the outer can 2, and the positive electrode lead body 15 was resistance welded to the bottom surface of the terminal body 9 after the insulating plate 10 was inserted.

[0065] For the electrolyte, a non-aqueous solution was prepared by dissolving LiCF3SO3 at a concentration of 0.7 mol / L in a mixed solvent of ethylene carbonate, propylene carbonate, and dimethoxyethane (volume ratio 1:1:3), and 3.5 mL of this was injected into the outer can 2. The injection was divided into three times, and the entire amount was injected while reducing the pressure in the final step. After the electrolyte was injected, the cover plate 7 was fitted into the upper opening of the outer can 2, and the inner periphery of the open end of the outer can 2 was welded to the outer periphery of the cover plate 7 by laser welding, sealing the opening of the outer can 2.

[0066] [Pre-discharge, aging] The sealed battery was pre-discharged at a resistance of 1 Ω for 30 seconds, stored at 70°C for 6 hours, and then subjected to a second pre-discharge at a constant resistance of 1 Ω for 1 minute to form a lithium-aluminum alloy on the separator side surface of the sheet-shaped negative electrode. The pre-discharged battery was aged at room temperature for 7 days, and the open circuit voltage was measured to confirm that a stable voltage was obtained, yielding a cylindrical lithium primary battery with an outer diameter of 17.0 mm and a total height of 50 mm.

[0067] Furthermore, 100 electrode bodies were produced and used to assemble batteries, but no batteries were found to have had problems with insertion of the electrode body into the outer casing.

[0068] Example 2 A metallic lithium foil having a width of 42 mm, a length of 99 mm, and a thickness of 0.29 mm, and a metallic lithium foil having a width of 42 mm, a length of 57 mm, and a thickness of 0.29 mm were arranged on a copper foil (negative electrode current collector) having a width of 43 mm, a length of 173 mm, and a thickness of 15 μm, with a 6 mm gap in the longitudinal direction. Furthermore, an aluminum foil having a width of 40 mm, a length of 99 mm, and a thickness of 6 μm and a width of 40 mm, a length of 57 mm, and a thickness of 6 μm were overlapped on the metallic lithium foil, to form a sheet-like negative electrode.

[0069] A cylindrical lithium primary battery was assembled in the same manner as in Example 1, except that the sheet-like negative electrode was used.

[0070] The distance between the folded portion of the negative electrode formed by the winding core during winding and the inner peripheral edge of the metallic lithium foil facing the inner surface of the positive electrode was approximately 1 mm, and the distance between the inner peripheral edge of the metallic lithium foil facing the outer surface of the positive electrode and the winding center was approximately 2 mm. Thus, a portion of approximately 2 mm wide where no lithium layer was laminated was formed on the negative electrode current collector from the winding center toward the positive electrode mixture layer on the outer surface of the positive electrode.

[0071] In the same manner as in Example 1, 100 electrode assemblies were produced and batteries were assembled, but no batteries were found in which the electrode assembly had a defective insertion when being inserted into the outer casing.

[0072] Comparative Example 1 A sheet-like negative electrode was constructed by placing a metallic lithium foil having a width of 42 mm, a length of 162 mm and a thickness of 0.29 mm on a copper foil having a width of 43 mm, a length of 173 mm and a thickness of 15 μm, and further placing an aluminum foil having a width of 40 mm, a length of 162 mm and a thickness of 6 μm on the metallic lithium foil.

[0073] The sheet-like negative electrode and two PE microporous films similar to those in Example 1 were stacked on top of each other, and in plan view, the electrodes were sandwiched between the winding cores at the same positions as those sandwiched between the winding cores in Example 1. 100 electrode bodies were produced in the same manner as in Example 1, and cylindrical lithium primary batteries were assembled.

[0074] In the process of inserting the electrode assembly into the outer can, insertion defects were confirmed in 17 of the 100 electrode assemblies produced.

[0075] The 100 wound electrode bodies of Example 1, Example 2, and Comparative Example 1 each had a certain degree of variation in winding diameter, but in the electrode bodies produced in Example 1 and Example 2, even the electrode body with the largest winding diameter did not exceed the upper limit of the winding diameter that can be inserted into the outer can, so no insertion failure occurred.

[0076] On the other hand, in the electrode body produced in Comparative Example 1, a continuous lithium layer was present at the center of the winding and on the negative electrode current collector that does not face the positive electrode and continues outward from the center of the winding, so that the inner winding diameter of the electrode body became large. As a result, some electrode bodies had winding diameters that exceeded the range that could be inserted into the outer can, resulting in insertion failures in a certain number of electrode bodies.

[0077] Comparative Example 2 Except for arranging the two metallic lithium foils with a gap of 20 mm in the longitudinal direction, a sheet-shaped negative electrode was produced in the same manner as in Example 1. Then, a cylindrical lithium primary battery was assembled in the same manner as in Example 1.

[0078] In addition, 100 electrode bodies were prepared and assembled into batteries in the same manner as in Example 1, but no batteries were confirmed to have been defective when inserting the electrode body into the outer can. Next, five batteries each of the cylindrical lithium primary batteries of Example 1, Example 2, and Comparative Example 2 and the cylindrical lithium primary battery of Comparative Example 1 that were not defective during the assembly process were continuously discharged at a current value of 40 mA at 20° C., and the discharge capacity was measured until the battery voltage reached 2.0 V. The average values ​​of the respective measured values ​​are shown in Table 1.

[0079] [Table 1]

[0080] In the cylindrical lithium primary batteries of Examples 1 and 2 in which two lithium layers were arranged on the negative electrode current collector at an interval of 6 to 12 mm in the longitudinal direction, and Comparative Example 1 in which a continuous lithium layer was arranged without any separation between the lithium layers, the lithium layer was sufficiently opposed to the positive electrode active material, so that the designed discharge capacity was obtained.

[0081] On the other hand, as described above, in the cylindrical lithium primary battery of Comparative Example 1, a lithium layer was continuously formed also on the center of the winding and on the negative electrode current collector that continued outward from the center of the winding and did not face the positive electrode, resulting in electrode bodies with winding diameters exceeding the upper limit of the design, which resulted in defects in the battery assembly process.

[0082] In addition, in the cylindrical lithium primary battery of Comparative Example 2, the distance between the two lithium layers was too wide, so that a portion of the positive electrode active material on the inner end side of the winding no longer faced the lithium layer, resulting in a decrease in the discharge capacity of the battery.

[0083] In Examples 1 and 2, the manganese dioxide content per unit area of ​​the positive electrode mixture layer was 0.205 to 0.227 g / cm per one side of the positive electrode current collector. 2 The lithium content of the negative electrode lithium layer is adjusted to the range of 0.014 to 0.017 g / cm per unit area according to the capacity of the positive electrode. 2 Since the thickness of the positive electrode mixture layer is adjusted to be too large, it is possible to realize a high capacity battery without making the thickness of the positive electrode mixture layer too large or the density of the positive electrode mixture layer too high.

[0084] On the other hand, the manganese dioxide content per unit area of ​​the positive electrode mixture layer is 0.227 g / cm per side of the positive electrode current collector. 2 If it exceeds this value, problems such as a decrease in the permeability of the electrolyte into the positive electrode mixture layer and defects due to a decrease in the flexibility of the positive electrode are likely to occur, resulting in an impediment to achieving a high capacity battery.

[0085] The present application can be implemented in other forms than those described above. The embodiments disclosed in the present application are merely examples and are not limited thereto. The scope of the present application shall be interpreted in accordance with the appended claims rather than the above description of the specification, and all modifications within the scope of the claims are intended to be included in the scope of the claims. [Explanation of symbols]

[0086] 1 Cylindrical lithium primary battery 2 Outer can 2a bottom 3 Electrode body 4 Positive electrode 5 Negative electrode 6 Separator 7 Lid plate 8 Insulating packing 9 Terminal body 10 Insulating plate 11 Base 12 Side wall 13 Gas vent 14 Insulating plate 15 Positive electrode lead body 16 Negative electrode lead body 18 Center of winding 30 Exposed part 31 Adhesive Tape 32 Laminate 33 Winding core 35 Horizontal groove 41, 42 Positive electrode mixture sheet (positive electrode mixture layer) 43 Positive electrode current collector 51 Lithium layer 51a Metallic lithium foil 51b Aluminum foil 52 Negative electrode current collector 61, 62 Separator

Claims

1. A cylindrical lithium primary battery including an electrode assembly formed by spirally winding a positive electrode and a negative electrode with a separator interposed therebetween, the positive electrode includes a positive electrode current collector and a positive electrode mixture layer that is disposed on both sides of the positive electrode current collector and contains manganese dioxide as a positive electrode active material, The manganese dioxide content per unit area of ​​the positive electrode mixture layer is 0.205 to 0.227 g / cm per one side of the positive electrode current collector. 2 and The negative electrode includes a negative electrode current collector and two lithium layers laminated on one surface of the negative electrode current collector and separated by an interval of 6 mm or more and 12 mm or less in the longitudinal direction, The two lithium layers each have a lithium content per unit area of ​​0.014 to 0.017 g / cm 2 and a negative electrode that is folded back between the two lithium layers at a position close to one of the lithium layers, the negative electrode current collectors overlap each other, and the negative electrode current collectors are wound such that inner peripheral ends of the two lithium layers are positioned outward from a winding center.

2. 2. The cylindrical lithium primary battery according to claim 1, wherein the negative electrode is folded back between the two lithium layers at a position within 1.5 mm of one of the lithium layers.

3. 2. The cylindrical lithium primary battery according to claim 1, wherein the negative electrode has a portion on the inner side of the stacked negative electrode current collectors where no lithium layer is laminated, the portion having a width of 2 mm or more from the center of the winding.

4. 2. The cylindrical lithium primary battery in accordance with claim 1, wherein the area of ​​said lithium layer is 83% or more of the area of ​​said negative electrode current collector.

5. 2. The cylindrical lithium primary battery according to claim 1, wherein the ratio of the lithium content per unit area of ​​the lithium layer to the manganese dioxide content per unit area of ​​the positive electrode mixture layer is 0.067 to 0.077 by weight.

6. 2. The cylindrical lithium primary battery according to claim 1, wherein 90% or more of the surface of the lithium layer facing the separator is alloyed with aluminum to form a lithium-aluminum alloy.

7. 7. The cylindrical lithium primary battery according to claim 6, wherein the ratio of the total amount of aluminum to the total amount of lithium contained in the lithium layer in which the lithium-aluminum alloy is formed is 0.095 to 0.105 by weight.

Citation Information

Patent Citations

  • Battery cell, battery cell winding method and battery

    CN112670596A

  • Nonaqueous electrolyte battery

    JP2004342452A

  • Cylindrical nonaqueous electrolyte solution battery

    JP2007250414A

  • Cylindrical nonaqueous electrolyte primary battery

    JP2012138225A

  • Cylindrical secondary battery

    WO2019065871A1